1979
DOI: 10.1111/j.1365-2621.1979.tb10061.x
|View full text |Cite
|
Sign up to set email alerts
|

Baking Properties of Plasma Protein Isolate

Abstract: 0, 2, 4, 6, 8 and 10% of commercial bread flour (14.3% protein on a d.w.b.) were replaced with bovine plasma protein isolate (96% protein on a d.w.b.) in a short-time dough bread making system. Loaf volume of the bread made with 2-6% PPI, was significantly higher than the control bread (100% wheat flour). Increasing levels of PPI darkened the crust and crumb colors and made the texture coarse and open. 2% of PPI produced bread with acceptable flavor and could increase the bread protein and lysine by 15% and 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…As the level of CBP increased, there was gradual increase of crude protein content in both the groups of cakes. The findings of Del Rio De Rays et al (1980) in CBP and Khan et al (1979) in bovine blood plasma also support the present finding. Ether extract of cakes with and without flavour were highest at 0% and lowest at 60% level of CBP and no significant differences were recorded between the cakes.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…As the level of CBP increased, there was gradual increase of crude protein content in both the groups of cakes. The findings of Del Rio De Rays et al (1980) in CBP and Khan et al (1979) in bovine blood plasma also support the present finding. Ether extract of cakes with and without flavour were highest at 0% and lowest at 60% level of CBP and no significant differences were recorded between the cakes.…”
supporting
confidence: 94%
“…By using bovine plasma protein isolates, Khan et al (1979) prepared angel food cakes and found better acceptability for colour of cakes with 30% bovine blood plasma and 70% inclusion of egg white. Increased level of blood plasma protein isolate resulted in unacceptable colour in angel food cakes.…”
mentioning
confidence: 98%
“…Each test is clearly described with regards to: (i) test definition and purpose, (ii) scope ± and list of ingredients, (iii) apparatus ± equipment, implements, containers and sizes, and potential suppliers for equipment, and (iv) procedural steps, types of measurements needed (example bread volume) and forms of data treatment. 79±83 Khan et al 84 examined the effect of blood plasma protein isolate (PPI) on bread baking quality. PPI (96% protein À%N Â 6.25) was a creamy white free flowing powder with 3±5% water.…”
Section: Breadmentioning
confidence: 99%
“…The majority of reports deal with egg white as the benchmark protein for cake formation. 85±94 The angel cake test was also applied to whey protein, 7,8,95 blood plasma protein 84,96 and powdered beef plasma. 97 Egg white (or test protein) is added to flour, sugar, acid salt and water and mixed to form cake batter which is then baked under well-defined conditions.…”
Section: Angel Cakementioning
confidence: 99%
“…Bovine blood foaming capacity is equivalent to that of egg protein (Khan et al, 1979;Tybor et al, 1975). However, foam stability of plasma is lower than egg white proteins (Raeker and Johnson 1995;Tybor et al, 1975).…”
Section: Introductionmentioning
confidence: 96%